4-Aminoantipyrine-derived Schiff base substituted novel symmetrical zinc (II) phthalocyanine photosensitizers: Design, synthesis, photophysical, and photochemical properties for photodynamic therapy of cancer - Yalazan, Halise; Omeroglu, Ipek; Durmuş, Mahmut; Kantekin, Halit (Elsevier, 2025)
In this study, new Zn-phthalocyanine compounds (ANTS-ZnPcsp/np), peripherally and non-peripherally substituted with 4-aminoantipyrine-derived Schiff base, were synthesized and characterized by FT-IR, NMR, MALDI-TOF, and UV-Vis spectroscopic techniques. The photophysical and photochemical properties of these compounds were investigated. The fluorescence quantum yield values were found to be 0.11 and 0.05 in DMSO for ANTS-ZnPcp and ANTS-ZnPcnp, respectively. The singlet oxygen quantum yield values of these phthalocyanines were obtained as 0.53 for ANTS-ZnPcp and 0.27 for ANTS-ZnPcnp. According to the results, both phthalocyanine derivatives are considered to be suitable photosensitizers for cancer treatment by photodynamic therapy (PDT) method.
Keywords: 4-Aminoantipyrine; Schiff base; Phthalocyanine; Photodynamic therapy; Photophysical; Photochemical